ความชุกและปัจจัยที่เกี่ยวข้องกับความเครียดจากการทำงานและภาวะเบื่องานในพนักงานต้อนรับบนเครื่องบิน บริษัท การบินไทย จำกัด (มหาชน) - กิตติพงษ์ เชี่ยวรุ่งโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
Analyzes the degree of the prevalence and its related factors of occupational stress and burnout among flight attendants of Thai Airways International Public Company Limited. The figure of 403 subjects included in this study obtained from Stratified sampling method and simple random sampling technique. The instruments consists of 5 parts ; 26-item questionnaire on demographic data, 18-item questionnaire on work factors, Muadsley Personality Inventory, The Personal Resource Questionnaire : PRQ Part II, and Occupational Stress and Burnout Inventory. Data was analyzed by SPSS for Windows. Statistical analyses included chi-square test, t-test, pearson product-moment correlation, one-way analysis of variance, multiple comparison : Scheffe s method, and stepwise multiple linear regression analysis. The findings revealed that occupational stress and burnout were present with a prevalence of 21.1% and 8.5% respectively. The chi-square test showed statistically significant difference in occupational stress and burnout at P<0.01 between neuroticism and stability, use and non-use of sedative drugs, with and without stressful life event within last 3 months. Whereas, personal income, family income, enough-to-spend economic status, and obligations towards family statistically significant difference at P<0.05. The scores on workload, time wasted due to in-operate equipments, job security, relationship among peers (helpful co-workers and support from colleagues), supervisor s support, freedome to express to supervisor, fairness of salary increase, company policies, day-off allowance, knowledges utilized in work, and flight scheduling statistically significantly difference at P<0.05 Scores on exercise significantly difference at P<0.01. Six predictive variables of occupational stress and burnout were neuroticism personelity, obligation towards family, the use of sedative drugs, disease, stressful life event within last 3 months, and working position.